Indirect effects of the covid-19 pandemic on childhood infection in England: population based observational study - Kadambari, S; Goldacre, R; Morris, E; Goldacre, MJ; Pollard, AJ (BMJ Publishing Group, 2022)
Objective To assess the impact of the covid-19 pandemic on hospital admission rates and mortality outcomes for childhood respiratory infections, severe invasive infections, and vaccine preventable disease in England.